2020
DOI: 10.21037/jtd-20-213
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA growth arrest specific-5: a potential biomarker for early diagnosis of severe asthma

Abstract: Background: The diagnosis of severe asthma (SA) is difficult due to a necessary long-term treatment history currently, while there are few studies on biomarkers in the diagnosis of SA. Long non-coding RNA (lncRNA) growth arrest specific-5 (GAS5) has the potential of playing this role because its binding with glucocorticoid receptor (GR). The purpose of this article is to explore the possibility of lncRNA GAS5 acting as a biomarker for early diagnosis of severe asthma (SA).Methods: Peripheral blood was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…LncRNA KCNQ1OT1 was correlated with the number of fibroblasts and functioned as a predictor of airway remodeling. Wu et al (2020) confirmed that lncRNA growth arrest specific-5 (GAS5) expressed differentially in PBMCs between nonsevere asthmatic patients and severe asthmatic patients. To further explore its mechanism, it was found that GAS5 could bind to the glucocorticoid receptor and affect its phosphorylation at serine 226 in human bronchial epithelial cells (HBECs) in vitro.…”
Section: Lncrnas Associated With Asmcs Proliferation In Asthma Pathogmentioning
confidence: 56%
“…LncRNA KCNQ1OT1 was correlated with the number of fibroblasts and functioned as a predictor of airway remodeling. Wu et al (2020) confirmed that lncRNA growth arrest specific-5 (GAS5) expressed differentially in PBMCs between nonsevere asthmatic patients and severe asthmatic patients. To further explore its mechanism, it was found that GAS5 could bind to the glucocorticoid receptor and affect its phosphorylation at serine 226 in human bronchial epithelial cells (HBECs) in vitro.…”
Section: Lncrnas Associated With Asmcs Proliferation In Asthma Pathogmentioning
confidence: 56%
“…Li et al have reported that GAS5 expression increased in PM2.5‐induced HBECs 13 . Similarly, a recent study indicated that GAS5 level was higher in peripheral blood mononuclear cells from asthma patients compared with patients with nonsevere asthma 14 . Moreover, pro‐inflammatory mediators could increase GAS5 expression in airway smooth muscle and epithelial cells 11 .…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with our results, Li et al revealed that silencing of FOXO3 inhibited NLRP3‐mediated pyroptosis in human aortic endothelial cells after treatment with oxidized low‐density lipoprotein. 14 In addition, FOXO3 inhibition abrogates inflammation and apoptosis of LPS‐induced alveolar epithelial cells, 36 which activates the Nrf2/HO‐1 pathway to inhibit LPS‐induced pyroptosis in human gingival fibroblasts 23 . An interaction between FOXO3 and the Nrf2/HO‐1 pathway could be inferred because FOXO3 is reported to directly interact with the promoter of Keap1 to inhibit the Nrf2 signaling pathway 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have looked at the possible function and potential of GAS5. [61][62][63] Wu et al found increased expression of GAS5 in peripheral blood of patients with severe and non-severe asthma compared with healthy controls. 63 GAS5 expression reduced after treatment with dexamethasone, a synthetic glucocorticosteroid, in a mouse model of steroid-insensitive asthma.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%